“SELLING” SELF-IMAGE IN THE ERA OF NEW MEDIA - Rulli Nasrullah (Humaniora, 2014)
The rise of citizen journalism gives the public an opportunity for producing news which has been previously controlled by the mass media institutions. In this case, the citizen acts not only a news consumer, but also as a news producer and consumer at the same time (prosumer). Based on these phenomena, this research tries to see how citizens carry out commodification. Analyses of computer-mediated communication with the media of Kompasiana reveal that space for citizen journalism has become a medium for self commodification in accordance with their target or values they want to achieve. The results of this research also show that the citizens used the media in order to gain personal motives such as to get material benefits or to build a self-image. In the level of media space, the facilities provided by Kompasiana like a description of profile and comment column can be used for prosumer activity. It is possible for the audience to employ this facility to promote the products or the users themselves as products. Based on research questions and findings in the field, some conclusions can be drawn. First, the presence of media citizen journalism no longer positions the audience as a passive audience entity, affected only by information produced by the media industry. Second, the audience is involved as a subject who gives information in citizen journalism for private interest such as for practical economic activity.